REDUPLIKASI BAHASA BUGIS: KAJIAN MORFOLOGI DISTRIBUSI - Mahabbatul Camalia (Kantor Bahasa Kalimantan Timur, 2016)
Every language has a particular form of reduplication, including Bugis language. It contains inflectional reduplications that are full and partial reduplications. Morphology distribution theory by Framptom is used to explain the reduplication process in Bugis language. The data collection technique uses observation method. Agih method is used to analyze the data. Also, the data display uses formal and informal methods. The study shows that morphemes in reciprocal forms affiliate with basic forms of verbs, morphemes in quantity forms affiliate with basic forms of numerals, and morphemes in stressing forms affiliate with basic forms of adjectives.